Association Between Hemoglobin A1C and Midurethral Sling Complications in Diabetic Women: A Cohort Study. Issue 6 (June 2021) - Ortega, Marcus V.; Bangura, Marie; Ayati, Elnaz; James, Kaitlyn; Mitchell, Caroline; Weinstein, Milena M.; Von Bargen, Emily
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2021;27:159–162) Stress urinary incontinence (SUI), affecting up to one third of the US adult population of women, is treated with pelvic floor muscle training, physical therapy, supportive devices including pessary, and surgery. The midurethral sling (MUS) is considered a standard of care surgical treatment given its low risk of complication and high success rate.